Biogeochemical analysis of ancient Pacific Cod bone suggests Hg bioaccumulation was linked to paleo sea level rise and climate change - Murray, Maribeth S.; McRoy, C. Peter; Duffy, Lawrence K.; Hirons, Amy C.; Schaaf, Jeanne M.; Trocine, Robert P.; Trefry, John (Frontiers in Environmental Science, 2015)
Deglaciation at the end of the Pleistocene initiated major changes in ocean circulation and distribution. Within a brief geological time, large areas of land were inundated by sea-level rise and today global sea level is 120 m above its minimum stand during the last glacial maximum. This was the era of modern sea shelf formation; climate change caused coastal plain flooding and created broad continental shelves with innumerable consequences to marine and terrestrial ecosystems and human populations. In Alaska, the Bering Sea nearly doubled in size and stretches of coastline to the south were flooded, with regional variability in the timing and extent of submergence. Here we suggest how past climate change and coastal flooding are linked to mercury bioaccumulation that could have had profound impacts on past human populations and that, under conditions of continued climate warming, may have future impacts. Biogeochemical analysis of total mercury (tHg) and 13C/15N ratios in the bone collagen of archaeologically recovered Pacific Cod (Gadus macrocephalus) bone shows high levels of tHg during early/mid-Holocene. This pattern cannot be linked to anthropogenic activity or to food web trophic changes, but may result from natural phenomena such as increases in productivity, carbon supply and coastal flooding driven by glacial melting and sea-level rise. The coastal flooding could have led to increased methylation of Hg in newly submerged terrestrial land and vegetation. Methylmercury is bioaccumulated through aquatic food webs with attendant consequences for the health of fish and their consumers, including people. This is the first study of tHg levels in a marine species from the Gulf of Alaska to provide a time series spanning nearly the entire Holocene and we propose that past coastal flooding resulting from climate change had the potential to input significant quantities of Hg into marine food webs and subsequently to human consumers.